A general review of the gastronomic dictionary material in Upper Imeretian sub-dialect - Mtskerashvili, Marina (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2023)
The foundation of any language lies in its lexical and grammatical structures. Lexical composition, derived from the lexical fund, forms the entire language system through grammatical structure. Languages evolve, incorporating dialectal words into their vocabulary. Dialectal vocabulary is crucial as it preserves diverse linguistic forms, facilitating comprehensive research. Therefore, a comprehensive review of gastronomic lexical material in the Upper Imerian dialect is essential. It aids in conserving regional culinary heritage, understanding local customs and traditions, and exploring the region›s food-related interactions. Studying the gastronomic lexicon of Upper Imeretian sub-dialect illuminates how this specific sub-dialect evolved under culinary traditions and unique cultural practices of the region. This research is imperative for safeguarding cultural traditions, linguistic dynamics, culinary identity, and sociolinguistic significance. Documenting the region›s culinary vocabulary helps protect Upper Imerian’s distinctive traditions and linguistic legacy, underscoring the significance of preserving and celebrating diverse cultural practices.